2012
DOI: 10.1097/meg.0b013e328355cc79
|View full text |Cite
|
Sign up to set email alerts
|

A combination of faecal tests for the detection of colon cancer

Abstract: The combination of i-FOBT and M2-PK is a sensitive tool in clinical practice for the appropriate management of waiting lists for colonoscopy, as it allows the classification of patients into different degrees of priority for investigation, according to their foreseeable risk of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…The difference in the serum level of tumor M2-PK between patients with CRC and healthy individuals was determined with a sensitivity of 98%, which was consistent with the results of the study [26] and exceeded the sensitivity of such methods as colonoscopy, occult fecal blood tests, levels of cancer-embryonic antigen, and the fecal M2-PK [27,28]. In the routine laboratory practice, the fecal M2-PK is determined using monoclonal antibodies specific to the dimeric form (immuno-enzyme analysis).…”
Section: Resultssupporting
confidence: 80%
“…The difference in the serum level of tumor M2-PK between patients with CRC and healthy individuals was determined with a sensitivity of 98%, which was consistent with the results of the study [26] and exceeded the sensitivity of such methods as colonoscopy, occult fecal blood tests, levels of cancer-embryonic antigen, and the fecal M2-PK [27,28]. In the routine laboratory practice, the fecal M2-PK is determined using monoclonal antibodies specific to the dimeric form (immuno-enzyme analysis).…”
Section: Resultssupporting
confidence: 80%
“…The sensitivity and specificity estimates for faecal immunochemical testing alone and CRC were 61.7% (95% CI 47.4% to 74.2%) and 88.8% (95% CI 84.1% to 92.3%), respectively; for the combination of faecal immunochemical testing and faecal calprotectin these estimates were 90.9% (95% CI 78.8% to 96.4%) and 35.9% (95% CI 29.7% to 42.6%), respectively; for faecal immunochemical testing and M2-PK, sensitivity and specificity were 91.5% (95% CI 80.1% to 96.6%) and 57.1% (95% CI 50.6% to 63.2%), respectively, and, for all of the three markers, they were 95.7% (85.7% to 98.8%) and 24.1% (18.8% to 30.2%), respectively. 142 Although all of the sensitivity estimates were generally lower, this pattern was repeated when the target condition was advanced neoplasia. 142 However, the FIT threshold in this study (20 µg Hb/g faeces) was higher than that which the results of our systematic review indicate is likely to be the optimal threshold (10 µg Hb/g faeces or a lower threshold).…”
Section: Clinical Effectivenessmentioning
confidence: 88%
“…142 Although all of the sensitivity estimates were generally lower, this pattern was repeated when the target condition was advanced neoplasia. 142 However, the FIT threshold in this study (20 µg Hb/g faeces) was higher than that which the results of our systematic review indicate is likely to be the optimal threshold (10 µg Hb/g faeces or a lower threshold). A second study 143 of accuracy for the target condition of advanced neoplasia, which did not meet the inclusion criteria for this assessment because it used a qualitative FIT method, also found that combining faecal calprotectin with faecal immunochemical testing (where a positive result was defined as either or both tests positive) resulted in increased sensitivity and decreased specificity [92% (95% CI 82% to 97%) and 49% (95% CI 43% to 54%)] compared with faecal immunochemical testing alone [74% (95% CI 62% to 83%) and 82% (95% CI 78% to 86%)].…”
Section: Clinical Effectivenessmentioning
confidence: 88%
See 2 more Smart Citations